The Berenstain bears go to camp - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923-2012. (New York : Random House, 1982)
The Berenstain cubs enjoy day camp, although they are dubious about the end-of-season pow-wow and sleep-out at the top of Skull Rock.
Keywords: Camps -- Fiction; Bears -- Fiction